ADOLESCENT-PARENT COMMUNICATION ON SEXUAL AND REPRODUCTIVE HEALTH AND ITS ASSOCIATED FACTORS AMONG HIGHER SECONDARY SCHOOL STUDENTS OF TOKHA MUNICIPALITY, NEPAL : A CROSS-SECTIONAL STUDY - Alisha Gautam; Krishna Sharma; Sunita Dhakal; Sarmila Dhakal; Anugraha Chand (Banyuwangi: Prodi Kesehatan Masyarakat PSDKU Universitas Airlangga Banyuwangi, 2023)
Background: As compared to other age groups, adolescents are more vulnerable to sexual and reproductive health issues. Parents can become protective and influencing factors for their children to prevent risky sexual behavior. Purpose: This study aimed to assess adolescent-parent communication on sexual and reproductive health and its associated factors. Methods: A descriptive cross-sectional study among 212 adolescents aged 15-19 in higher secondary schools of Tokha Municipality. A self-administered structured modified questionnaire to assess the communication used the Weighted Topics Measure of Family Sexual Communication tool with a simple random sampling technique. Descriptive statistical analysis and chi-square tests were used to analyze data and assess the association between variables. Data quality was assured through careful questionnaire design, pretesting, and training. Results: The study found that 75.9% of adolescents had communicated on sexual and reproductive health (SRH) topics with their parents, 24.1% never communicated,  47.2% seldom communicated on SRH topics, followed by sometimes (23.6%) and often (5.2%), respectively. Adolescent-parent communication on SRH was significantly associated with the level of knowledge regarding sexual and reproductive health (ꭓ2 = 5.809, p-value = 0.01, df = 1). Similarly, there was a significant association with the perceived parenting style (ꭓ2 =3.932, p-value =0.04, df =1), living arrangements (ꭓ2 =6.376, p-value=0.01, df =1), and adolescent-parent communication. Conclusion: It concluded that adolescent-parent communication on SRH issues is not satisfactory. Creating an adolescent-friendly environment at home and conducting awareness programs with the help of the local government of the respective schools would help to increase adolescent-parent communication.